2017
DOI: 10.15296/ijwhr.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Behaviors and Self-efficacy of Physical Activity During Pregnancy: An Interventional Study

Abstract: Maintaining a health-promoting lifestyle is defined as controlling certain behaviors and selecting appropriate behaviors in the daily life for one's own health (1). Healthpromotion behavior is a multifaceted model of perception, self-initiated action or practice (2). It is a response to World Health Organization's (WHO's) goal of "health for all" (3). According to Pender, health promoting lifestyle behaviors include nutrition, exercise, stress management, health responsibility, spiritual improvement, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Although, available health promotion approaches have recently emphasized the benefits of PA, a stronger focus should be placed on promoting women’s beliefs about their own self-efficacy to enhance their confidence in overcoming obstacles to participate in regular physical activities [ 36 , 39 ]. In this study, self-efficacy was one of the significant predictor that showed a relatively significant proportion of the total effects in PA (16.1%), which was consistent with the Pender’s HPM and previous studies in Iran [ 13 , 41 ]. Despite significant negative effects of interpersonal influences on self-efficacy, this construct has emerged as a significant predictor because most of participants (64%) possessed a positive sense and belief concerning the benefits of PA.…”
Section: Discussionsupporting
confidence: 91%
“…Although, available health promotion approaches have recently emphasized the benefits of PA, a stronger focus should be placed on promoting women’s beliefs about their own self-efficacy to enhance their confidence in overcoming obstacles to participate in regular physical activities [ 36 , 39 ]. In this study, self-efficacy was one of the significant predictor that showed a relatively significant proportion of the total effects in PA (16.1%), which was consistent with the Pender’s HPM and previous studies in Iran [ 13 , 41 ]. Despite significant negative effects of interpersonal influences on self-efficacy, this construct has emerged as a significant predictor because most of participants (64%) possessed a positive sense and belief concerning the benefits of PA.…”
Section: Discussionsupporting
confidence: 91%
“…Health promoting lifestyle emphasizes on life-improving behaviors such as regular exercising, eating nutritious foods, managing stress, avoiding high-risk behaviors, creating satisfying relationships with friends, and having a goal in life [2, 16, 17]. The health-related behaviors of the individual are problematic despite the much evidence about the benefits of healthy behaviors [18]. While women are seeking safe ways to spend the pregnancy period in a healthy manner as soon as they get pregnant and they are going to make positive behavioral changes, [17, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, most housework chores are done by married women, and in addition to housework, they may also have a job outside their home. Women with multiple roles may suffer from more stress and strain due to the high pressure of their responsibilities and the lack of leisure time [19][20][21][22]. The results of a study showed that there is a relationship between a husband's involvement in housework and his wife's psychosocial health, which in turn helps improve her psychosocial health [23].…”
Section: Introductionmentioning
confidence: 99%